Do Not Leave Your Language Alone : The Hidden Status Agendas Within Corpus Planning in Language Policy - Fishman, Joshua A. (Mahwah, New Jercy Lawrence Erlbaum Associates, 2006)
"This book, focused on corpus planning in language policy, provides a broad, integrative framework and also discusses multiple languages in detail. It provides readers with great familiarity with a wide range of language cases and at the same time gives them the theoretical tools and analysis to see how they inter-relate." "Written at an introductory level assuming no prior knowledge of the field, this book is intended as a text for higher undergraduate and lower graduate level courses in language planning and policy. It is equally valuable for researchers in the field of language planning, policy, and politics, as well as those in sociolinguistics, political science, and communication studies more generally."--Jacket.
Include Maps, Appendix and Index
Keywords: Language planning. -- Language policy